Designing Dynamic Organizations / A hands-on guide for leaders at all levels - Downey Diane; Galbraith Jay; Kates Amy (Addison-Wesley Publishing Company, 2002)
Preface, Acknowledgements, Getting Started, Determing the Design Framework, Designing the Structure, Processes and Lateral Capability, Defining and Rewarding Success, People Practices, Implementation, Conclusion.
Preface, Acknowledgements, Getting Started, Determing the Design Framework, Designing the Structure, Processes and Lateral Capability, Defining and Rewarding Success, People Practices, Implementation, Conclusion.